2011
DOI: 10.1017/s0266467411000538
|View full text |Cite
|
Sign up to set email alerts
|

Covariation between understorey light environments and soil resources in Bornean mixed dipterocarp rain forest

Abstract: Variation in understorey irradiance is both a cause and consequence of the structure and dynamics of closed-canopy forests, which are also influenced by soil nutrients and water availability. We tested the hypothesis that understorey light regimes differ among four mixed dipterocarp forest types that share the same rainfall, but grow on different soils along an edaphic gradient at one site in Borneo. Based on data from photosynthetically active radiation sensors deployed at 1-m height at 36 locations for 351 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…For example, early ontogenetic stages such as seedlings and saplings typically have leaf traits that allow them to maintain positive carbon balance in light-limited environments (Dalling et al 1998, Thomas and Winner 2002, Poorter et al 2005, often resulting in stronger abiotic filtering of leaf traits in low-light environments for saplings relative to adults (Laurans et al 2012, Dent et al 2013. In contrast, canopy adults in high-light environments may be more strongly limited by soil resources, resulting in stronger abiotic filtering of leaf traits across soil-resource gradients (Russo et al 2012). In addition, the strength of abiotic filtering may vary among ontogenetic stages if seedlings and saplings are more sensitive to density-dependent biotic interactions (Webb and Peart 1999, Harms et al 2000, Wright 2002, Metz et al 2010, resulting in stronger biotic filtering of traits in early life-history stages (Paine et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, early ontogenetic stages such as seedlings and saplings typically have leaf traits that allow them to maintain positive carbon balance in light-limited environments (Dalling et al 1998, Thomas and Winner 2002, Poorter et al 2005, often resulting in stronger abiotic filtering of leaf traits in low-light environments for saplings relative to adults (Laurans et al 2012, Dent et al 2013. In contrast, canopy adults in high-light environments may be more strongly limited by soil resources, resulting in stronger abiotic filtering of leaf traits across soil-resource gradients (Russo et al 2012). In addition, the strength of abiotic filtering may vary among ontogenetic stages if seedlings and saplings are more sensitive to density-dependent biotic interactions (Webb and Peart 1999, Harms et al 2000, Wright 2002, Metz et al 2010, resulting in stronger biotic filtering of traits in early life-history stages (Paine et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We found that dipterocarps in the volcanic site demonstrated the greater RGR than those in the sedimentary site at the smallest size class (Table 4). Light conditions in the understory can co-vary with soil nutrient availability (Coomes and Grubb 2000;Russo et al 2012), and therefore nutrient and light may be involved in the greater RGR of the volcanic site. We found that the ratio of trees with shaded crown (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Soils derived from aged geological substrates in the tropics are highly weathered due to the hot and humid climate, and often contain very low concentrations of total phosphorus (P) (e.g. 49-340 µg g -1 total P for topsoils in the Bornean rain forests; Proctor et al 1983, Baltzer et al 2005, Russo et al 2012. The decrease in total P is associated with a reduction of plantavailable P (Johnson et al 2003), which is known to be the factor that frequently limits productivity and structure among tropical lowland forests (Elser et al 2007, Vitousek et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In Bornean rainforests Russo et al (2012) found that understorey light availability is highest in forests growing on soils of intermediate fertility. However, this result was partly due to differences in topography between soil types, and the studied soil nutrient gradient was shorter than in our study, corresponding to internal variation within the Nauta formation.…”
Section: Stem Density Measurements and Light Availabilitymentioning
confidence: 99%
“…However, this result was partly due to differences in topography between soil types, and the studied soil nutrient gradient was shorter than in our study, corresponding to internal variation within the Nauta formation. Russo et al (2012) measured the understorey light availability in different forests directly with sensors of photosynthetic photon flux density. Our measurements of canopy openness and stem density were meant to be indirect measures of understorey light environment, but we acknowledge that stem density is not necessarily linearly related to light availability in the understorey, as is evidenced by the white-sand forests which have both a high stem density and high light in the understorey.…”
Section: Stem Density Measurements and Light Availabilitymentioning
confidence: 99%